2022
DOI: 10.1038/s41598-022-25662-9
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the benefits of school-based, peer-led interventions for leaders

Abstract: The aim of our systematic review and meta-analysis was to quantitatively synthesise the effects of school-based peer-led interventions on leaders’ academic, psychosocial, behavioural, and physical outcomes. Eligible studies were those that: (i) evaluated a school-based peer-led intervention using an experimental or quasi-experimental study design, (ii) included an age-matched control or comparison group, and (iii) evaluated the impact of the intervention on one or more leader outcomes. Medline, Sportdiscus, Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Two results are worth noting: First, focus group members did not exhibit the same downstream trend as other students. Aligning with Wade et al (2022), this suggests that social referents may be the primary beneficiaries of such interventions. Second, we found that Create mechanisms for sustainment, such as leadership programs, independent implementation of the social referent approach by the staff individual students with high or partial exposure to the school-wide action led by social referents retained high average scores on outgroup tolerance compared to individuals who did not participate in the action, suggesting potential short-term (but not long-term) positive effects on tolerance resulting from peerled actions demonstrating equality-based respect and tolerance, which was suggested as one mechanism through which social referents can influence perceived norms and behaviors.…”
Section: Discussionmentioning
confidence: 97%
“…Two results are worth noting: First, focus group members did not exhibit the same downstream trend as other students. Aligning with Wade et al (2022), this suggests that social referents may be the primary beneficiaries of such interventions. Second, we found that Create mechanisms for sustainment, such as leadership programs, independent implementation of the social referent approach by the staff individual students with high or partial exposure to the school-wide action led by social referents retained high average scores on outgroup tolerance compared to individuals who did not participate in the action, suggesting potential short-term (but not long-term) positive effects on tolerance resulting from peerled actions demonstrating equality-based respect and tolerance, which was suggested as one mechanism through which social referents can influence perceived norms and behaviors.…”
Section: Discussionmentioning
confidence: 97%